1993
DOI: 10.1002/jnr.490350212
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor changes G protein levels and localization in PC12 cells

Abstract: Growth cones at the growing tips of developing neurites contain the machinery to transmit information from receptors to a variety of intracellular enzymes and ion channels. In order to understand how signals are transmitted across the membrane, we asked whether the multiplicity of signalling pathways in the growth cone is reflected by the diversity of G proteins found in this organelle. Our immunohistochemical analysis indicated that growth cones of differentiated PC12 cells contain at least 4 alpha G protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…The distribution of G o␣ in Fig. 5 is consistent with previous studies (26,33). Similar results were obtained when we used anti-G o1 antibody (data not shown).…”
Section: Ps-1 Binds G O In a Gtp␥s-dependent Manner-to Precisely Charsupporting
confidence: 91%
“…The distribution of G o␣ in Fig. 5 is consistent with previous studies (26,33). Similar results were obtained when we used anti-G o1 antibody (data not shown).…”
Section: Ps-1 Binds G O In a Gtp␥s-dependent Manner-to Precisely Charsupporting
confidence: 91%
“…It is highly expressed in brain and endocrine cells. It has been reported that levels of Gnao protein are elevated in NGF-treated PC12 cells (14)(15)(16) as well as concentrated in growth cones (16). Consistent with this, our SAGE analysis revealed a 10-fold induction of Gnao transcripts in response to NGF treatment.…”
Section: Guanine Nucleotide Binding Protein Alpha O (Gnao)supporting
confidence: 88%
“…Many studies have described changes of ␣ and ␤␥ subunits, for example, in cellular differentiation (Watkins et al, 1987;Asano et al, 1989;Brabet et al, 1991;Zubiaur and Neer, 1993) and organ development (Milligan et al, 1987;Asano et al, 1988b;Luetje et al, 1988) or in response to hormones such as thyroid hormone (Ros et al, 1988;Rapiejko et al, 1989) and steroids (Chang and Bourne, 1987). However, these studies have not addressed the question that is the subject of the present study, namely whether or not their expression is coordinated such that the total levels of ␣ and ␤␥ subunits are equal to each other.…”
Section: Introductionmentioning
confidence: 97%